A remessa necessária no código de processo civil de 2015 e seus desdobramentos na atuação da advocacia pública : problema ou solução? - Menezes, Felipe Barbosa de (2016)
The Code of Civil Procedure of 2015 updated the rules concerning compulsory appeal, bringing about important innovations in this legal instrument, especially with regard to the limits of procedural prerogatives. This paper aims to discuss compulsory appeal under the new CCP, in order to demonstrate specifically that the legislator’s choice to determine their unsuitability in cases with sentences that reproduce binding guidelines signed under the administrative aegis of the public entity involved in the litigation (Art. 496, par. 4) allows for the compatibility between the aforementioned legal instrument and the jurisdictional control exercised by public attorneys over legal action practiced by the Brazilian Administration, which also encompasses the framework of rights and interests presented in court by public authorities that disregard the law, as interpreted and applied by the jurisprudence of Brazilian courts. The problem presented by the previous legal regime was that taking a case back to court – as mandated by compulsory appeal, even when public authorities found themselves in favor of the plaintiff’s case (by withholding all appeals and defense, recognizing the plaintiff’s complaint, celebrating agreements, etc.) – prevented the lawsuit’s successful resolution in the first instance, which hampered the efficacy of public attorneys’ jurisdictional control in their litigative duties. This issue seems to have been corrected by the CCP of 2015, specifically by Article 496, paragraph 4, item IV, which bars the use of compulsory appeal in returning a case to court over sentences that overturn the legal arguments made by the public attorneys, thus allowing for a dispute’s resolution in the first instance